Temporary restorative materials used by Brazilian Dental Schools during and after endodontic treatment (Revista da Faculdade de Odontologia - UPF, 2013)
Objective: this study aimed at evaluating which temporary restorative materials are recommended by Brazilian Dental Schools (BDS), during and after endodontic treatment completion. Methods: a questionnaire was distributed to all 191 BDS, and returned by 55 (28.8%)schools. Topics of interest included: which temporary restorative materials are advised in different remaining dental conditions and different permanence periods in the mouth, minimum material thickness, intermediate material application, use of matrix band and factors influencing material selection. Results: the answers showed that the remaining coronal tooth structure significantly interferes with the choice of temporary restorative materials. On the other hand, time between ap pointments does not have significant influence on material selection. Still, premixed hygroscopic materials are recommended in cases of simple endodontic access (occlusal or lingual/palatal) if the material will be kept for up to one week in the month. Glass ionomer cement (GIC) is the most commonly used material in long periods, especially for access cavities involving proximal surfaces or fractured cusps. The utilization of an intermediate material is very variable and some schools do not advocate any material. Most BDS recommend a minimum thickness of 3 mm for temporary restorations and the use of matrix band in proximal surfaces. Conclusion: BDS choices with respect to coronal sealing materials are driven especially by remaining dental conditions.